Liver Kinase B1 Regulates Remodeling of the Tumor Microenvironment in Triple-Negative Breast Cancer - King, Connor T.; Matossian, Margarite D.; Savoie, Jonathan J.; Nguyen, Khoa; Wright, Maryl K.; Byrne, C. Ethan; Elliott, Steven; Burks, Hope E.; Bratton, Melyssa R.; Pashos, Nicholas C.; Bunnell, Bruce A.; Burow, Matthew E.; et al. (Frontiers in Molecular Biosciences, 2022)
Liver kinase B1 (LKB1) is a potent tumor suppressor that regulates cellular energy balance and metabolism as an upstream kinase of the AMP-activated protein kinase (AMPK) pathway. LKB1 regulates cancer cell invasion and metastasis in multiple cancer types, including breast cancer. In this study, we evaluated LKB1's role as a regulator of the tumor microenvironment (TME). This was achieved by seeding the MDA-MB-231-LKB1 overexpressing cell line onto adipose and tumor scaffolds followed by the evaluation of tumor matrix-induced tumorigenesis and metastasis. Results demonstrated that the presence of tumor matrix enhanced tumorigenesis in both MDA-MB-231 and MDA-MB-231-LKB1 cell lines. At the same time, metastasis was only increased in the MDA-MB-231 cell line seeded on tumor scaffold. Endpoint analysis of tumor and adipose scaffolds revealed LKB1 mediated TME remodeling as evident through altered matrix protein production. Proteomic analysis determined that LKB1 overexpression preferentially decreased all major and minor fibril collagens (collagens I, III, V, and XI). In addition, proteins observed to be absent in tumor scaffolds in the LKB1 overexpressing cell line included those associated with adipose matrix (COL6A2) and regulators of adipogenesis (IL17RB, IGFBP4), suggesting a role for LKB1 in tumor mediated adipogenesis. Histological analysis of MDA-MB-231-LKB1 seeded tumors demonstrated decreased total fibril collagen and indicated decreased stromal cell presence. In accordance with this, in vitro condition media studies demonstrated that the MDA-MB-231-LKB1 secretome inhibited adipogenesis of adipose-derived stem cells. Taken together, these data demonstrate a role for LKB1 in regulating the tumor microenvironment through fibril matrix remodeling and suppression of adipogenesis.